A girl named Disaster - Farmer, Nancy (New York : Puffin Books, 1996)
While fleeing from Mozambique to Zimbabwe to escape an unwanted marriage, Nhamo, an eleven-year-old Shona girl, struggles to escape drowning and starvation and in so doing comes close to the luminous world of the African spirits.
"A Richard Jackson book"--Half t.p.
Keywords: Shona (African people) -- Juvenile fiction; Shona (African people) -- Fiction; Survival -- Fiction; Supernatural -- Fiction